Response of spatial structure of cotton root to soil-wetting patterns under mulched drip irrigation - Li, Dongwei; Li, Mingsi; Shen, Xiaojun; Zhou, Xinguo; Sun, Hao; Zhao, Yulong; Chen, Wenjuan (International Journal of Agricultural and Biological Engineering, 2020)
The matching relationship between the spatial structure of cotton cluster root systems and soil-wetting patterns under mulched drip irrigation forms the theoretical basis for the technical design of mulched drip irrigation. A 2-year field experiment was conducted, in which different soil-wetting patterns were produced by setting different emitter discharge rates. The envelopes of cotton cluster root length densities were derived using the topological methodology and used to examine the effects of different soil-wetting patterns on the spatial structure of root systems and water uptake capacity within row spaces. The results showed that the root systems in rows of cotton grown under narrower and deeper soil-wetting patterns exhibited a single-peak distribution, while those under wider and shallower soil-wetting patterns exhibited a two-peak distribution. Furthermore, cotton rows grown near mulch edges experienced lower moisture stress, and wider and shallower soil-wetting patterns contributed to greater root growth rates in the vertical direction and resulted in more even potential water uptake capacities. The findings of this study revealed that wider and shallower soil-wetting patterns were more desirable for mulched drip irrigation of cotton and should be considered in the technical design of drip irrigation systems.Keywords: mulched drip irrigation, soil-wetting pattern, envelopes of cotton cluster root length densities, soil matrix suction, potential root water uptake capacityDOI: 10.25165/j.ijabe.20201305.5790Citation: Li D W, Li M S, Shen X J, Zhou X G, Sun H, Zhao Y L, et al. Response of spatial structure of cotton root to soil-wetting patterns under mulched drip irrigation. Int J Agric & Biol Eng, 2020; 13(5): 153–162.